TIMING AND THE AMPHIBIOUS LANDING PLACE IN THE WATERS OF TUBAN BEACH BASED ON ASPECTS OF METEO – OCEANOGRAPHY - Muhammad Nur Candra; Supriyanto Supriyanto; Teguh Herlambang (Indonesian Naval Technology College STTAL, 2021)
Amphibious operation integrates various types of force that ships, aircraft, and landing troops in an attack on enemy beaches and or potentially controlled by the enemy and marine nature in the sense that the Navy took the lead role as reflected in the way the implementation of such operations. Wind and rainfall information, wave, depth, tide, and currents as well as the characteristics of known absolute Tuban beach. Plot Wr analysis method Tuban beach waters wind, waves and currents follow the pattern of monsoon circulation, while the harmonic analysis is known that the type of tidal waters Tuban beach entrance in a single daily group. Basic morphology Tuban coastal waters are generally very gentle slopes to a depth of 30 m and partly sandy, muddy, and quicksand coastal waters. Wind speed max of 14.87 knots. The rainfall max of 56 mm/hr. The significant wave height of 0.6 m and a wave period of 4.6 s.The High Waters Level of 180 cm and Low Waters Level of 40 cm and Mean Sea Level of 140 cm. The max speed of 76.47 cm/s. Keywords: Amphibious Operations, Meteo-Oceanographic aspects, Wr plot analysis method and harmonic analysis, bathymetry.